Survey of Puree Users without Smoking History of Households in Kosebo Village, Angata District, Konawe Selatan District - Ruslan Majid; Elma Prasetyaningsih; Fikki Prasetya; Jumakil; Fifi Nirmala (Indian Journal of Forensic Medicine & Toxicology, 2021)
“Puree” in the local language is a process of concocting or mixing tobacco and whiting, finally forming ablack paste and then rubbing it on the lips, the user. “Me puree” in local language terms is using “Puree”.The purpose of this study was to determine the survey of Puree Users with no smoking history amonghousewives in Kosebo Village, Angata District, South Konawe Regency in 2019. This research method useda descriptive method, carried out in Kasebo Village, Angata District, South Konawe Regency. The populationof all housewives was 203. The sampling technique used was proportional random sampling, and obtained anumber of 54 respondents. The results of the research after analyzing the frequency distribution showed thatthe respondents’ knowledge was lacking, the history of using “puree” was sufficient, the tradition of “puree”users was good, the income of “Puree” users was less and the previous disease history of “puree” users wasless. It is recommended that a primitive program to provide public health education by conducting outreachto identify risk factors that can increase the incidence of both smokeless and smoked tobacco use.